Role of the molecular structure of carboxylate-alumoxanes in the enhanced nucleation of polypropylene - Mani, Mohan Raj; Chellaswamy, Ramesh; Marathe, Yogesh N.; Pillai, Vijayamohanan K. (Chemical Communications, 2015)
We have reported the use of carboxylate-alumoxanes as efficient nucleating agents for isotactic polypropylene (iPP) with a possible structural correlation to the nucleation efficiency. The unique, butterfly-like structure of carboxylate-alumoxanes correlates well with the nucleation characteristics of iPP and, for the first time, the impact of a thermally induced, crystalline transition of carboxylate-alumoxanes, which alters neither the structural conformation nor the nucleation efficiency of the transformed material, is demonstrated.